Timeliness of Autism Spectrum Disorder Diagnosis and Use of Services among U.S. Elementary School-Aged Children - Zuckerman, Katherine (Psychiatr Serv, 2016)
OBJECTIVE: This study assessed the relationship of timeliness of ASD diagnosis with current use of ASD-related services in a nationally-representative sample of U.S. children. METHODS: The CDC’s Survey of Pathways to Diagnosis and Services was used to assess experiences of 722 children age 6–11 with ASD. Bivariate and multivariate associations between age and delay in ASD diagnosis and use of health services were explored. Older age of diagnosis was defined as diagnosis at age 4 years or older. Delay in diagnosis was defined as time ≥2 years between first discussion of concerns with provider and ASD diagnosis. Health services included current use of behavioral intervention therapy (BI), school-based therapy, complementary/alternative medicine (CAM), and psychotropic medications. RESULTS: Mean age of ASD diagnosis was 4.4 years, and mean diagnostic delay was 2.2 years. On adjusted analysis, diagnosis at ≥4 years old was associated with lower likelihood of current BI or school-based therapy use. Diagnosis at ≥4 years old was also associated with higher likelihood of current psychotropic medication use. Likelihood of current psychotropic medication use increased with older age of ASD diagnosis. A ≥2 year delay in diagnosis was associated with higher likelihood of current CAM use. Likelihood of current CAM use increased as delay in diagnosis got longer. CONCLUSIONS: Both older age of diagnosis and longer delay in diagnosis were associated with different health services utilization patterns among younger children with ASD. Prompt and early diagnosis may be associated with increased use of evidence-based therapies for ASD.